Synthesis and plasma pharmacokinetics in CD‐1 mice of a 18β‐glycyrrhetinic acid derivative displaying anti‐cancer activity. (16th November 2012) - Lallemand, Benjamin; Ouedraogo, Moustapha; Wauthoz, Nathalie; Lamkami, Touria; Mathieu, Veronique; Jabin, Ivan; Amighi, Karim; Kiss, Robert; Dubois, Jacques; Goole, Jonathan
Abstract Objectives The plasma pharmacokinetic profile in CD‐1 mice of a novel 18β‐glycyrrhetinic acid (GA) derivative, which displays in vitro anti‐cancer activity, was assessed. Methods This study involved an original one‐step synthesis of N‐(2‐{3‐[3, 5‐bis(trifluoromethyl)phenyl]ureido}ethyl)‐glycyrrhetinamide, (2) a compound that displays marked anti‐proteasome and anti‐kinase activity. The bioselectivity profile of 2 on human normal NHDF fibroblasts vs human U373 glioblastoma cells was assessed. Maximal tolerated dose (MTD) profiling of 2 was carried out in CD1 mice, and its serum pharmacokinetics were profiled using an acute intravenous administration of 40 mg/kg body weight. Key findings Compound 2 displayed IC50in vitro growth inhibitory concentrations of 29 and 8 μm on NHDF fibroblasts and U373 glioblastoma cells, respectively, thus a bioselectivity index of ∼4. The intravenous pharmacokinetic parameters revealed that 2 was rapidly distributed (t1/2dist of ∼3 min) but slowly eliminated (t1/2elim = ∼77 min). Conclusions This study describes an original and reliable nanoemulsion of a GA derivative with both anti‐proteasome and anti‐kinase properties and that should be further tested in vivo using various human xenograft or murine syngeneic tumour models with both single and chronic intravenous administration.